2007
DOI: 10.1084/jem.20062432
|View full text |Cite
|
Sign up to set email alerts
|

Thromboxane A2 is a key regulator of pathogenesis during Trypanosoma cruzi infection

Abstract: Chagas' disease is caused by infection with the parasite Trypanosoma cruzi. We report that infected, but not uninfected, human endothelial cells (ECs) released thromboxane A2 (TXA2). Physical chromatography and liquid chromatography-tandem mass spectrometry revealed that TXA2 is the predominant eicosanoid present in all life stages of T. cruzi. Parasite-derived TXA2 accounts for up to 90% of the circulating levels of TXA2 in infected wild-type mice, and perturbs host physiology. Mice in which the gene for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
125
0
2

Year Published

2008
2008
2012
2012

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 96 publications
(133 citation statements)
references
References 63 publications
(74 reference statements)
3
125
0
2
Order By: Relevance
“…Atherosclerosis is accelerated by diabetes and is associated with increased levels of TXA 2 and other eicosanoids that stimulate TP (14). TP expression and plasma levels of TP ligands are elevated, both locally and systemically, in several vascular and thrombotic diseases (17). Importantly, TP activation induces EC apoptosis (15,18) and prevents tube formation (19) by inhibiting Akt phosphorylation (18).…”
mentioning
confidence: 99%
“…Atherosclerosis is accelerated by diabetes and is associated with increased levels of TXA 2 and other eicosanoids that stimulate TP (14). TP expression and plasma levels of TP ligands are elevated, both locally and systemically, in several vascular and thrombotic diseases (17). Importantly, TP activation induces EC apoptosis (15,18) and prevents tube formation (19) by inhibiting Akt phosphorylation (18).…”
mentioning
confidence: 99%
“…There is evidence of increased production of endothelin in Chagas disease (Tanowitz et al, 2005). Many of the sequelae associated with T. cruzi infection are reminiscent of the effects of TXA2, including enhanced platelet adherence and aggregation in T cruzi-infected mice, where TXA2 levels are increased (Ashton et al, 2007;Cardoni and Antunez, 2004;Tanowitz et al, 1990). In T. cruzi, prostaglandin production, including TXA2 and PGF2 , is possible through a NADPH flavin oxidoreductase named "old yellow enzyme" (Kubata et al, 2002).…”
Section: Microvascular Abnormalities and Ischemiamentioning
confidence: 99%
“…T. cruzi derived TXA2 is important in modulating disease pathogenesis in the absence of host-derived TXA2. Ashton et al (Ashton et al, 2007) demonstrated that TXA2 is an important factor in Chagas disease that controls parasite proliferation and the resulting inflammatory response to the infection. TXA2 is a potent proinflammatory agent that activates and facilitates cytokine production by monocytes (Caughey et al, 1997;Ganzinelli et al, 2009).…”
Section: Microvascular Abnormalities and Ischemiamentioning
confidence: 99%
“…Another possibility is that microvascular damage may be indirectly initiated by the parasite, as it has been shown that T. cruzi calreticulin, which helps the parasite evade the host immune system by modulating the complement system, also inhibits angiogenesis in vivo [24]. Additionally, T. cruzi produce several bioactive lipids such as thromboxane A and prostaglandin F2α which are potent vasoconstrictors that also promote vascular permeability, vascular smooth muscle cell proliferation, and platelet aggregation [25]. Further evidence of T. cruzi-induced microvasculature damage includes observations that the parasites subvert the bradykinin system, activating bradykinin B 2 receptors during invasion of endothelial cells, resulting in vasodilation and subsequent edema [26].…”
Section: Damage To Cardiac Microvasculaturementioning
confidence: 99%